2000
DOI: 10.1159/000024359
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Human Neutrophil Functions by the 45-kD Glycoprotein Derived from the Parasitic Nematode <i>Trichinella spiralis</i>

Abstract: Aim: We evaluated the effect of the 45-kD protein of Trichinella spiralis (gp45), purified by affinity chromatography, on random migration and chemotaxis, the oxidative metabolism of human neutrophils and on the CD11b upregulation induced by formyl-methionyl-leucyl-phenylalanine (f-MLP). Methods: Donor neutrophils incubated with different amounts of gp45 (0.5, 1, 1.5, 2 μg/ml) or buffer and the random migration and chemotaxis, evaluated by means of a special technique of image analysis, and the chemiluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…For example, nematode infection influences the neuropeptide content of the gut (9), and it has been reported that infecting nematodes can modulate their environment by immunosuppression through the release of immunoreactive neuropeptides (14). It has also recently been reported that the 45-kDa glycoprotein derived from T. spiralis has an anti-inflammatory effect (6). In addition, goblet cell hyperplasia is a hallmark of T. spiralis infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nematode infection influences the neuropeptide content of the gut (9), and it has been reported that infecting nematodes can modulate their environment by immunosuppression through the release of immunoreactive neuropeptides (14). It has also recently been reported that the 45-kDa glycoprotein derived from T. spiralis has an anti-inflammatory effect (6). In addition, goblet cell hyperplasia is a hallmark of T. spiralis infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the host immune response will make it easier to identify the critical measures taken by parasites for evasion and prolonged infestation. Increasing evidence shows that parasite-derived substances play an important role in initiating or maintaining the parasite's advantage, directly suppressing the function of certain subsets of immune cells as well as stimulating other cell populations related to immunopathology (7,12,23).…”
Section: Discussionmentioning
confidence: 99%
“…Eggs hatch inside the female uterus and new larvae migrate through blood vessels to the striated muscles, where new cysts are formed. During this process, products excreted/secreted (ES) by T. spiralis induce profound effects on the host immune system, deviating Th1 responses to Th2 by inducing dendritic cells (DCs) and macrophages to acquire an immature, tolerogenic phenotype [34][35][36][37]. In addition to Th2 biasing, T. spiralis induces secretion of IL-10 and TGF-β by both innate and adaptive immune populations, contributing to regulation and containment of host tissue inflammation and fostering tissue repair [34,38].…”
Section: Abbreviationsmentioning
confidence: 99%